Association Between Periodontal Disease and Obesity in Young and Middle-Aged Adults - Tariq, Maliha; Ali, Asma Wahid; Hameed, Marij; Lodhi, Wajeeha (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate any possible correlation of obesity with periodontitis in young and middle-aged adults. Study Design: Cross-sectional study Place and Duration of Study: Periodontology Department, Institute of Dentistry, Combined Military Hospital, Medical and Dental College, Lahore from Dec 2022 to Mar 2023. Methodology: Subjects reporting to dental outpatient department aged 22 – 45 years old, with at least twelve permanent teeth and a negative history for smoking and diabetes were selected. Height and weight of selected subjects was measured to calculate BMI and subjects categorized as normal, overweight or obese. Periodontal pocket depth was ascertained using Michigan O Probe with William’s markings of ≥01 teeth from each sextant. Presence or absence of periodontitis was noted and classified according to severity of clinical attachment loss. Data analysis was done using descriptive statistics via SPSS. Chi-squared test was used to explore association of obesity and periodontitis. p≤0.05 was taken as significant. Results: Obesity was prevalent in 54(38.3%) of the subjects while periodontitis was seen in 93(66%) subjects. A statistically significant association between periodontitis and obesity was observed (p<0.001), with periodontitis being more prevalent in overweight and obese individuals. Periodontitis was also significantly associated with age of the subjects with increased frequency in subjects aged 35-45 years (p=0.002). Conclusion: A positive and significant association between periodontitis and obesity was observed (p<0.001), where overweight and obese individuals were more prone to suffer from periodontitis.